การจัดเก็บข้อมูลลักษณะรูปแบบรองเท้าที่มีจำหน่ายใน ตลาดอำเภอเมือง จังหวัดเชียงใหม่ เพื่อการจำแนกประเภทรอยพื้นรองเท้า - สุภาภรณ์ ทาสม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Shoe prints are generally found in the scene of crime, for example, shoe print stains with clay on the concrete ground or impressions in the sand. Normally such prints originated from the swell parts. This research has been done by photographing 200 pairs of shoes from Chiang Mai market in order to analyze in qualitative method. Each side of the shoe is then divided into two parts, namely the toe and the heel. The second step is to classify according to geometric patterns. This research proved that the right and the left side of each pair have the same qualifications without any significant differences. The variety of patterns can be identified to different group classifications, for example, sandals and cut-shoes. Moreover, some patterns are found in specific type of shoes only, for example, canvas shoes. It is noticeable that trademarks, alphabets or any other codes are usually found at the end part of the shoes. However, even general patterns are the same, but their details are different, for example, the size of patterns, the amount of the codes and their trails form manufacturing. The findings of this research is hopefully be useful for crime scene investigation in the future.